2021
DOI: 10.1158/1078-0432.ccr-20-2984
|View full text |Cite
|
Sign up to set email alerts
|

The Genetic Evolution of Treatment-Resistant Cutaneous, Acral, and Uveal Melanomas

Abstract: Purpose: Melanoma is a biologically heterogeneous disease composed of distinct clinicopathologic subtypes that frequently resist treatment. To explore the evolution of treatment resistance and metastasis, we used a combination of temporal and multilesional tumor sampling in conjunction with whole-exome sequencing of 110 tumors collected from 7 patients with cutaneous (n = 3), uveal (n = 2), and acral (n = 2) melanoma subtypes. Experimental Des… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 51 publications
1
8
0
Order By: Relevance
“…However, Luo et al. reported the difference between JAK1 and JAK2 , with JAK1 deficiency being able to mediate resistance to anti-PD-L1 immunotherapy while JAK2 could not ( 82 ), consistent with a recent report that metastases with JAK2 loss-of-function might be regressing under immunotherapy ( 83 ). As for the LOH or heterozygous mutations of the IFN-γ signaling genes, retaining a wide type allele, the tumors are still under effective immune attack ( 84 , 85 ).…”
Section: Underlying Mechanisms Of Arsupporting
confidence: 78%
“…However, Luo et al. reported the difference between JAK1 and JAK2 , with JAK1 deficiency being able to mediate resistance to anti-PD-L1 immunotherapy while JAK2 could not ( 82 ), consistent with a recent report that metastases with JAK2 loss-of-function might be regressing under immunotherapy ( 83 ). As for the LOH or heterozygous mutations of the IFN-γ signaling genes, retaining a wide type allele, the tumors are still under effective immune attack ( 84 , 85 ).…”
Section: Underlying Mechanisms Of Arsupporting
confidence: 78%
“…Much of the existing postmortem melanoma research has been limited to bulk DNA sequencing data (8,10,11). The inclusion of additional data modalities, namely transcriptomics and single-cell sequencing data in our study, revealed novel findings with clinical and technical implications.…”
Section: Discussionmentioning
confidence: 75%
“…Our study expands on previous multilesional metastatic melanoma analyses (8)(9)(10)(11)62) by increasing the number of patients studied, the number of samples per patient and the breadth of represented sites of metastases, as well as the breadth of multiomic data generated. We observe a number of different evolutionary routes to lethality.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Skin melanoma is among the most metastatic human cancers and is also among those with the highest tumor mutation burden (TMB~10 3 ) due to UV-induced carcinogenesis [ 1 ]. Furthermore, chromosomal instability (CIN) results in a high frequency of copy number variations (CNV) in a similar range as TMB as determined by the highest resolution technologies such as whole genome sequencing (WGS) or whole exome sequencing (WES) [ 2 ]. Meanwhile the TMB and CNV of melanoma are not strictly tightened together [ 3 ].…”
Section: Introductionmentioning
confidence: 99%